Coincidencias conceptuales entre el pensamiento débil y fin del arte en Vattimo y arte poshistórico en Danto : el "acontecimiento" Warhol - Caballero Bernané, José Fredy (2017)
This work develops the coincidences between the weak thinking in Vattimo and the posthistoric art in Danto, exemplified in the work of Warhol. Contemporary art and its philosophy emerge as a contestation movement against the canonical meta-narrative in art and show points of encounter with the postmodern philosophy that also criticized the metarrelates of history for its erection as totalizing ideologies. This research shows the closeness of Vattimo to Lyotard's analysis, and also to the Heideggerian concept of Dasein as to manifest and hide the truth; closeness to the Gadamerian concept of meaning as the possibility of achieving a collective experience of art without conceptualization. Vattimo indicates the possibility of access to the truth of the work of art through the ontology of non-being and shows the opportunity to be able to understand non-canonical art but historically. Danto characterizes contemporary art as post-historical art and considers the "Warhol event" as evidence, since what is after the history of the end of art can be "anything" capable of becoming a work of art and whose freedom of expression is unprecedented. Thus, Danto defines contemporary art as the propitious time for the philosophy of art.